Foundations of Software Science and Computation Structures: 28th International Conference, FoSSaCS 2025, Held as Part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025, Hamilton, ON, Canada, May 3–8, 2025, Proceedings (Lecture Notes in Computer Science, 2025)
This open access book constitutes the proceedings of the 28th International Conference on Foundations of Software Science and Computation Structures, FOSSACS 2025, which took place in Hamilton, Canada, during May 2025, held as part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025. The 19 papers included in these proceedings were carefully reviewed and selected from 58 submissions. They focus on foundational research in software science on theories and methods to support the analysis, integration, synthesis, transformation, and verification of programs and software systems.